Women’s Discourse in Novel Al-Ḥubb fī Zamān al-Naft: A Corpus-Based Qāsim Amīn Perspective - Ferawati Ferawati; Saifulah Samsudin; Muhammad Syukri Abdurrahman (Universitas Ahmad Dahlan, 2026)
This article examines women’s discourse in Nawāl as-Saʿdāwī’s Al-Ḥubb fī Zamān al-Naft through corpus linguistics-based literary research and Qāsim Amīn’s reformist perspective. The study responds to the limited integration of corpus evidence, textual quotation analysis, and Islamic reformist thought in Arabic literary criticism. It applies to an explanatory sequential mixed-methods design: the first stage produces quantitative corpus evidence, while the second stage provides qualitative interpretation through selected quotations from the novel. The corpus consists of 28,419 tokens and 9,327 types, with a vocabulary density of 0.328, a readability index of 9.818, and a mean sentence length of 29.1 words. Sixty-one quotations were selected through purposive sampling and categorized into six thematic fields. The findings show that women’s discourse is constructed through profession and work, education, hijab, marriage, divorce, and socio-political participation. Profession and work form the dominant discourse with 33 quotations or 54.1%, followed by education and hijab with 10 quotations or 16.4% each, marriage with 5 quotations or 8.2%, divorce with 2 quotations or 3.3%, and socio-political participation with 1 quotation or 1.6%. Close reading of Arabic quotations shows that women are represented as rational, speaking, working, educated, and socially negotiated subjects. The study contributes to Arabic literary studies by demonstrating how corpus-based thematic distribution can guide Qāsim Amīn-based interpretation of women’s discourse in modern Arabic fiction.